Reconfiguring digital education policy through youth leadership to support the achievement of the Sustainable Development Goals - Muhammad Irsad Maulana Khilman Asy-Syafi'i; Moh Fadhli Romadhon; Natia Natia; Indi Ramadhani Sitorus; Zalfa Afrillia (Priviet Social Sciences Journal, 2026)
Digital education inequality remains a major challenge in achieving the Sustainable Development Goals (SDGs), particularly SDG 4, 9, 10, and 17. Educational technology is viewed as a transformative instrument, yet gaps in access, digital literacy, and policy capacity indicate a weak orientation toward equity. This study aims to analyze the urgency of reconfiguring digital education policy by positioning youth leadership as a strategic actor. The study adopts a qualitative approach with a conceptual analysis based on a literature review. Data are drawn from policy documents and official publications of reputable international institutions, such as UNESCO, OECD, UNICEF, and the World Bank. Analysis is conducted through thematic analysis and critical policy analysis. The findings show that the digital divide is driven not only by infrastructure limitations, but also by low digital literacy, policy asynchrony, and minimal youth involvement. This study formulates youth leadership–based conceptual solutions, including strengthening the edutech ecosystem, equity-oriented adaptive learning, digital skills credentials, and expanding access in vulnerable regions. Reconfiguring digital education policy based on youth leadership is a strategic prerequisite for the sustainable contribution of digital education to the achievement of the SDGs.